AUDITOR SWITCHING MEMODERASI PENGARUH AUDIT TENURE PADA KUALITAS AUDIT - Metta Yustia, Wiguna; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
This study aims to know back influence audit tenure on the quality of an audit and to see if the auditors switching will moderating influence audit tenure on the quality of audit. The population s in this study are all the manufacturing companies listed on the Indonesia stock exchange in 2011-2014. Sampling method used is the method the non probability with the purposive sampling technique. The number of samples that are used in this research is the company's 106. Data collection methods used in this research is a method of observation of the non participant. The data analysis techniques used to solve those problems, namely a logistic regression analysis (logistic regression) using regression Analysis Regression model of Moderation (MRA). Based on the results of the analysis of switching auditors note that weakens the influence of the audit the audit on the quality of tenure. The results of the analysis shows that the audit of tenure has no effect on the quality of audits. The results of the analysis also showed the auditor switching weakens the influence of the audit the audit on the quality of tenure.
Keywords: auditor switching, audit tenure, quality of audits